Carcinoma of Vagina in Utero-Vaginal Prolapse: A Rare Presentation & Literature Review (Journal of Chittagong Medical College Teachers' Association, 2014)
Primary vaginal carcinoma is a rare entity in gynaecological oncology. Genital prolapse associated with primary carcinoma of vagina is even more rare. We here report two cases of early stage of vaginal carcinoma associated with utero-vaginal prolapse treated by surgery & radiotherapy and the review of literature of same entity. A 65 yrs old post menopausal lady presented with irreducible utero-vaginal prolapse & foul smelling per vaginal discharge. A fungating growth was present on the middle part of rt. antero-lateral wall of vagina. Biopsy was taken from the growth & histopathology showed squamous cell Ca. A 75 yrs old multiparous lady presented with long standing ulcer in association with second degree uterovaginal prolapse. Biopsy of the ulcer revealed squamous cell Ca of vagina. As one of the most complicated therapeutic problems in gynaecological oncology, this disease had been deemed to be untreatable until the end of 1930s. Presently as a result of technological improvements in radiotherapy & radical surgery, more favourable prognosis are to be achieved. A patient with a long history of uterine prolapse must be treated with care due to the risk potential for malignant change. Any lesion associated with utero-vaginal prolapse need careful evaluation & should be subjected to biopsy to rule out the underlying carcinoma.JCMCTA 2014 ; 25 (2) : 61-64